2015
DOI: 10.1039/c5ra00610d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, stabilization, growth behavior, and catalytic activity of highly concentrated silver nanoparticles using a multifunctional polymer in an aqueous-phase

Abstract: Highly concentrated Ag nanoparticles (above 20 g L−1) synthesized by the reaction AgNO3 with BPEI exhibited long-term stability over more than 40 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 67 publications
2
51
0
Order By: Relevance
“…Average sizes of the Ag NPs were (15.8±3.5), (24.2±5.9), and (42.9±12.4) nm at weight ratios of 5, 7, and 11, respectively (Figure b–d and Figure S6 b–d in the Supporting Information). In previous works on the synthesis of Ag NPs with PEI as a stabilizer, it was demonstrated that the Ag ion and PEI could make a PEI−Ag complex; thus modulating the reaction rate …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average sizes of the Ag NPs were (15.8±3.5), (24.2±5.9), and (42.9±12.4) nm at weight ratios of 5, 7, and 11, respectively (Figure b–d and Figure S6 b–d in the Supporting Information). In previous works on the synthesis of Ag NPs with PEI as a stabilizer, it was demonstrated that the Ag ion and PEI could make a PEI−Ag complex; thus modulating the reaction rate …”
Section: Resultsmentioning
confidence: 99%
“…The catalytic reactions are of tremendous interest because of a fundamental significance and broad technological applications. Metal NPs with small sizes and narrow distributions are most attractive because of their low cost and high electrocatalytic activity owing to their large surface‐to‐volume ratios . In the catalytic reaction, the stability of the catalyst is of prime interest because catalysts often lose their catalytic activity owing to the formation of aggregates or surface poisoning under harsh reaction conditions .…”
Section: Resultsmentioning
confidence: 99%
“…Because BPEI is known as a weak reducing agent, we believe that BPEI prevented the surface oxidation of the Cu NWs. 21,24,25 In previous research on the synthesis of Ag nanoparticles using BPEI in an aqueous-phase, we reported that the protonated amine groups of BPEI have a weaker ability to stabilize Ag nanoparticles under strong acidic conditions. After several washing and storing 40 days at room temperature, we found that thin CuO layer were formed on the surface of NWs.…”
Section: Introductionmentioning
confidence: 99%
“…21 We could partially remove the BPEI by several washing the Cu NWs using ethanol. 21 When the synthesis was conducted under strong acidic conditions (pH = 1.8), thick and short Cu NWs were observed, showing the weak stabilization ability of BPEI ( Fig. XRD and XPS results show the presence of CuO layer on the surface of NWs while major crystal structure was still metallic Cu (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In comparison with other metal nanoparticles with catalytic activity, [3][4][5] such as Pt and Pd nanoparticles, [6,7] AgNPs can be prepared more readily and inexpensively, so they have attractive application prospect in catalysis. [8] However, like other colloidal metal nanoparticles, colloidal AgNPs dispersed in aqueous medium are prone to self-aggregation and settling down owing to their high surface energy and great density, [9] In recent years, stimulus-responsive nanofibrous hydrogel consisting of randomly or orderly aligned nanofibers with the diameters of less than 1000 nm has attracted more and more attention, which overcome the above-mentioned disadvantages of smart bulky hydrogels and microgels. [23] First, it is able to respond rapidly to external stimulus due to very small diameters of their constituent nanofibers and porous structure, which facilitates the transfer of the stimulus to the whole material.…”
Section: Introductionmentioning
confidence: 99%